Procuratores – imperial agents or curators’ assistants? - Kamińska, Renata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
For the first time procuratores aquarum were nominated by Emperor Claudius. Their main task was to help curators to perform their duties. Together with them, prosecutors supervised the distribution of public water in Rome. In fact, the real purpose of establishing the office of procuratores aquarum was to exercise control over the activities of curatores aquarum. This was due to Claudius’ attempt to limit the role of the Senate whose representatives held the procuratores offices. However, Frontinus in his treatise De aquaeductu urbis Romae as a rule accused them of fraud and various abuses they committed during the mandate. This shows that Claudius’ aim for this office was not fully realized. Procuratores were more likely to be remembered as public water thieves than curators.

Po raz pierwszy procuratores aquarum zostali powołani przez cesarza Klaudiusza. Ich głównym zadaniem było pomaganie kuratorom w wypełnianiu przez nich ich obowiązkow. Wraz z nimi prokuratorzy nadzorowali dystrybucję wody publicznej na terenie Rzymu. Jednak prawdziwym celem utworzenia urzędu procuratores aquarum było sprawowanie przez nich kontroli nad działalnością curatores aquarum. Wynikało to z dążenia Klaudiusza do ograniczenia roli senatu, którego przedstawiciele sprawowali urzędy prokuratorskie. Jednak Frontinus w swoim traktacie De aquaeductu urbis Romae oskarżał ich o kradzieże i różne inne nadużycia, które pełnili w czasie kadencji. To pokazuje, że cel, jaki nadał temu urzędowi Klaudiusz, nie do końca został zrealizowany. Prokuratorzy bowiem dali się raczej zapamiętać jako złodzieje wody publicznej niż pomocnicy kuratorów.
Keywords: procuratores aquarum; curatores aquarum; public water; woda publiczna